2008
DOI: 10.1016/j.geb.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Information aggregation in auctions with an unknown number of bidders

Abstract: Information aggregation, a key concern for uniform-price, common-value auctions with many bidders, has been characterized in models where bidders know exactly how many rivals they face. A model allowing for uncertainty over the number of bidders is essential for capturing a critical condition for information to aggregate: as the numbers of winning and losing bidders grow large, information aggregates if and only if uncertainty about the fraction of winning bidders vanishes. It is possible for the seller to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In a double‐auction setting with many goods, Harstad, Pekec, and Tsetlin (2008) and Atakan and Ekmekci (2021) considered the effect of numbers uncertainty on the information aggregation properties of a k th‐price auction (Pesendorfer and Swinkels (1997)). In Harstad, Pekec, and Tsetlin (2008), the distribution of bidders is exogenously given.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a double‐auction setting with many goods, Harstad, Pekec, and Tsetlin (2008) and Atakan and Ekmekci (2021) considered the effect of numbers uncertainty on the information aggregation properties of a k th‐price auction (Pesendorfer and Swinkels (1997)). In Harstad, Pekec, and Tsetlin (2008), the distribution of bidders is exogenously given.…”
Section: Related Literaturementioning
confidence: 99%
“…In a double‐auction setting with many goods, Harstad, Pekec, and Tsetlin (2008) and Atakan and Ekmekci (2021) considered the effect of numbers uncertainty on the information aggregation properties of a k th‐price auction (Pesendorfer and Swinkels (1997)). In Harstad, Pekec, and Tsetlin (2008), the distribution of bidders is exogenously given. Harstad, Pekec, and Tsetlin (2008) found that even if the equilibrium strategy is strictly increasing (which aids aggregation), information aggregation fails unless the numbers uncertainty is negligible.…”
Section: Related Literaturementioning
confidence: 99%
“… See also Harstad et al (2008) for the effect of an uncertain number of bidders in the large double‐auction setting of Pesendorfer and Swinkels (1997). …”
mentioning
confidence: 99%
“… Harstad, Pekec, and Tsetlin () develop a theory for common‐value auctions with uncertainty over the number of bidders.…”
mentioning
confidence: 99%